Care Homes in Spain in the COVID-19 Pandemic: Lessons Learned from an Intervention by Médecins Sans Frontières - Maria Ximena Di Lollo; Elena Estrada Cocina; Francisco De Bartolome Gisbert; Raquel González Juarez; Ana Garcia Mingo (Journal of Humanitarian Affairs, 2021)
When the COVID-19 pandemic struck in early 2020, it rapidly became apparent that older individuals were at greater risk of serious illness and death. The risk was even greater for residents in care homes, who live in close proximity and may be suffering other comorbidities. Such facilities also saw a high turnover of staff and visitors, meaning an increased risk of transmission. Data has suggested that care home residents may account for up to a half of all COVID-related deaths in Spain.